Pemberdayaan Masyarakat untuk Peningkatan Pengetahuan dan Kualitas Hidup Terkait Kesehatan Gigi di Kelurahan Sukarami Kota Palembang - Widodo, Yufen; Hamid, Abu; Nurhayati, Masayu; Mujiyati, Mujiyati (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
Health education is one of the promotive and preventive efforts to deliver health messages to communities, groups, or individuals with the hope of increasing better health knowledge. One of the targets in the health sector of health promotion is community empowerment. The community is the primary target that must be empowered, so that they can maintain and improve health .Pre test knowledge of the community in RT 28 RW 10 and RT 15 RW 13, Sukarami Village is still in the category of less than 27%, enough is 50%, while for the good category is 23%, before being given counseling on how to maintain family oral health. Post test knowledge of the community of RT 28 RW 10 and RT 15 RW 13, Sukarami Village is still in the good category by 77% and sufficient by 23%, after being given counseling on how to maintain family oral health